Carbon Quantum Dot as Electron Transporting Layer in Organic Light Emitting Diode - Alam M.B.; Yadav K.; Shukla D.; Srivastava R.; Lahiri J.; Parmar A.S. (My University, 2025)
Carbon quantum dots derived from banana leaves by a simple hydrothermal process has been used as an electron transport layer to fabricate Organic Light Emitting Diodes. To the best of our knowledge, this is the first report of Carbon QD utilized as an electron transport layer inOLED. Devices with multilayered structureITO/PEDOT: PSS/PFO/CQD/LiF/Al are fabricated on indium tin oxide (ITO) coated glass substrates. Current-Voltage (I−V) curves reveal that the turn-on voltages are reduced from 8 V to 6 V as compared with pristine PFO device.Results show CQD as an ETL has enhanced the performance and efficiency of the OLEDs. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim